ONLINE TA‘ĀRUF, DIGITAL VISUALIZATION, AND THE LIMITS OF VIEWING ‘AWRAH: A HADITH-BASED REINTERPRETATION IN ISLAMIC LAW WITHIN THE DIGITAL BETROTHAL PROCESS - Usman; Safitri, Nuri; Ahmad Failasuf Nasuha (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2026)
Purpose - This study was motivated by the prevalence of online ta‘āruf practices that rely on the exchange of photos and visualizations of women's bodies, giving rise to debates about the limits of viewing the ‘awrah in Islamic law. This study aims to analyze this permissibility through a reinterpretation of the hadiths on khiṭbah and to formulate normative and ethical boundaries for viewing women's ‘awrah that are relevant to the characteristics of digital media in online ta‘āruf practices. Methods - This qualitative study used a normative-contextual approach. Primary data were sourced from the Instagram social media account @taaruf. co.id as an online ta‘āruf service provider and khiṭbah hadiths. Secondary data included fiqh literature, hadith commentary, and contemporary studies on digital ethics and online ta‘āruf . Data analysis was conducted through tracing the 'illat (legal rationale), contextual reading, and normative-ethical analysis of online ta’aruf practices. Findings – This study found a new form of online ta‘āruf practice characterized by repeated visual exchanges, image storage, and visual consumption that is not always accompanied by a clear commitment to marriage. The reinterpretation of the khiṭbah hadiths was carried out by repositioning the 'illat of the permissibility of seeing, from mere visual permissibility to a limited means for making the decision to marry and preventing future regret. Based on this repositioning, this study formulates normative boundaries for viewing women's ‘awrah that emphasize the connection between permissibility and the goal of marriage. This study reformulates the ethics of viewing women’s ‘awrah in online ta‘āruf, which includes respect for women's karāmah, moral responsibility, goal orientation, and self-control in the digital space. Contribution/limitations - This study contributes to the development of contemporary Islamic legal ethics by offering a relational ethical framework for users and online ta‘āruf platforms, although it is still limited to normative studies and requires reinforcement through further empirical research.